Let us use basic algebraic proofs. We begin by using X and Y as any rational value.
Let X and Y be equal values | X = Y | |
---|---|---|
Multiply boths sides by X | X^{2} = XY | |
Subtract boths sides with Y^{2} | X^{2} - Y^{2} = XY - Y^{2} | |
Factor each side | (X - Y)(X + Y) = Y(X - Y) | |
Divide by (X - Y) | X + Y = Y | |
Since X = Y, substitute Y with X | X + X = X | |
Simplify | 2X = X | |
Divide by X | 2 = 1 |
Obviously, there is an error in this proof. Can you find it? Simply make your guess by clicking on any of the steps (in bold letters) that you think may be logically flawed. Most are correct, and we will tell you that below. But once you find the correct one, we will explain why and tally your score below.
Attempts: 0